ANALISIS KAWASAN KESELAMATAN OPERASI PENERBANGAN (KKOP) BANDAR UDARA PEKON SERAI DI KABUPATEN LAMPUNG BARAT - Putra, Andius Dasa; Purba, Alexander (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2009)
As the one requirement for air transport safety and airport operating is Obstacle LimitaionSurface (OLS) area. The aimed of this research is to determining the major obstacle limitationsurface, consist of take-off and landing surface, possibility accident area, conical area, innerhorizontal, outer horizontal, transition area, and instrument of navigation posistion. This researchas inputing program to Pemerintah Daerah Kabupaten Lampung Barat to prevent of high buildingand tower BTS who would be disturb or give the risk for air transport operation at the SeraiAirport. Based on the observation and geodetic calculation we can determining of ObstacelLimitaion Surface (OLS) area at Serai Airport. Thsi research shown that high building and towerBTS by height about 70 – 120 m, not enter in this area of obstacle limitation surface.Furthermore, Pemerintah Kabupaten Lampung Barat will prepare and make a regulation abouthow many height of building who considered will be allowed in the Obstacel Limitation Surface(OLS) area.